Birth order and child health - Evelina Björkegren; Helena Svaleryd (Uppsala University, Department of Economics, 2017)
Previous research has established that birth order affects outcomes such as educational achievements, IQ and earnings. The mechanisms behind these effects are, however, still largely unknown. In this paper, we examine birth-order effects on health, and whether health at young age could be a transmission channel for birth-order effects observed later in life. We find no support for the birth-order effect having a biological origin; rather firstborns have worse health at birth. This disadvantage is reversed in early age and later-born siblings are more likely to be hospitalized for injuries and avoidable conditions, which could be related to less parental attention. In adolescence and as young adults, younger siblings are more likely to be of poor mental health and to be admitted to hospital for alcohol induced health conditions. We also critically test for reverse causality by estimating fertility responses to the health of existing children. We conclude that the effects on health are not severely biased; however, the large negative birth-order effects on infant mortality are partly due to endogenous fertility responses. Overall our results suggest that birth order effects are due to differential parental investment because parents' time and resources are limited.
urn:nbn:se:uu:diva-317441
Keywords: J13; J24; I12; 330; Birth order; child health; parental behavior; endogenous fertility